Material Models and Properties in the Finite Element Analysis of Knee Ligaments: A Literature Review - Galbusera, Fabio; Freutel, Maren; Dürselen, Lutz; D’Aiuto, Marta; Croce, Davide; Villa, Tomaso; Sansone, Valerio; Innocenti, Bernardo (Frontiers in Bioengineering and Biotechnology, 2014)
Knee ligaments are elastic bands of soft tissue with a complex microstructure and biomechanics which are critical to determine the kinematics as well as the stress bearing behavior of the knee joint. Their correct implementation in terms of material models and properties is therefore necessary in the development of finite element models of the knee, which has been performed for decades for the investigation of both its basic biomechanics and the development of replacement implants and repair strategies for degenerative and traumatic pathologies. Indeed, a wide range of element types and material models has been used to represent knee ligaments, ranging from elastic unidimensional elements to complex hyperelastic three-dimensional structures with anatomically realistic shapes. This paper systematically reviews literature studies which described finite element models of the knee, and summarizes the approaches which have been used to model the ligaments highlighting their strengths and weaknesses.